The Economic and Social Impact of the Novel Coronavirus (Covid-19) on Migrant Remittances: An Overview of Tunisia and Morocco - Hajer Habib (Global Labor Organization (GLO), 2020)
The spread of the novel coronavirus and 'stay at home' measures in response to this global health crisis is profoundly changing societies and economies around the world. The objective of this work is to analyze the economic impact of Covid-19 by focusing on their implications on migrant remittances flows in Tunisia and Morocco. Indeed, we analyze in which countries, where individuals depend on remittances and where this dependence intersects with economic vulnerability and inadequate financial infrastructure. We use micro-data from the Afrobarometer survey, wave 2016-2018. Based on Principal Component Analysis (PCA), the results show that the decline in remittances will exacerbate economic difficulties during the crisis for individuals who depend on remittances. In Tunisia, 60% of individuals who say they are dependent on remittances are unemployed and 46% of those who say they are dependent on remittances face a lack of liquidity. In Morocco, 63% and 43%, respectively the share of individuals who say they are dependent on remittances are unemployed and the share with liquidity problems. Also, "stay at home" measures are likely to limit the ability of individuals to receive funds from abroad. Both countries have similar access to infrastructure, more than 46% of people who depend on remittances do not have a bank account and 37% do not have access to the internet. They would therefore be less able to adapt to a restriction on in-person remittance services during a lockdown to contain the Covid-19 virus. For this reason, the paradigm shift from cash to digital money is necessary.
Keywords: F22; F24; O15; I10; R2; 330; Remittances; Covid-19; Economic vulnerability; Principal Component Analysis (PCA)